Rapid identification of anti‐inflammatory compounds from Tongmai Yangxin Pills by liquid chromatography with high‐resolution mass spectrometry and chemometric analysis. Issue 11 (6th May 2015) - Tao, Shan; Huang, Yi; Chen, Zhui; Chen, Yaqi; Wang, Yi; Wang, Yi
<x xml:space="preserve">Abstract</x> We present an integrated approach to rapidly identify anti‐inflammatory compounds of TongmaiYangxin Pills (TMYXP), a botanical drug for the treatment of cardiovascular disease. Liquid chromatography coupled with high‐resolution mass spectrometry was used to analyze the chemical composition of TMYXP. Eighty compounds of TMYXP including flavonoids, coumarins, iridoid glycosides, saponins, and lignans, were identified unambiguously or tentatively. After the rapid isolation and bioassay, 18 fractions of TMYXP were obtained and their anti‐inflammatory activities were evaluated in lipopolysaccharide‐stimulated RAW 264.7 macrophages. We performed chemometric analysis to reveal the correlation between the chemical and pharmacological information of the fractions to facilitate the identification of active compounds. To verify the reliability of the proposed method in discovering active components from a complex mixture, activities of seven compounds, which were positively or negatively related to bioactivity according to calculation, were validated in vitro. Results indicated that six active compounds with high R values exerted certain anti‐inflammatory effects in a dose‐dependent manner with IC50 values of 53.6–204.1 μM. Our findings suggest that the integrated use of identification based on high‐resolution mass spectrometry and chemometric methods could rapidly identify active compounds from complex mixture of natural products.